The Impact of Electronic games on the intelligence of the Students of First Episode in Omdurman Topical (Experimental study for Basic stage in Khartoum state) - Abuelgasem, Hiba Ahmed Bashora; Mohmed, Bakhita Mohmed Zain (Journal of Educational and Psychological Sciences, 2020)
The aim of this study was to know the effect of electronic games programs on the level of intelligence for the first episode students in Khartoum State. To achieve this goal, the researchers used the semi- experimental, one- group approach, and both tribal and post- test. The original study population included 450 students, the study sample was randomly selected. It consisted of (27) students of the first seminar in the Al- Qabas primary school in Omdurman. The students ranged in age from (6- 9) years.The tools of the study in the standard of the intelligence of John- Raven stained color on the Sudanese environment Mehd Al- Mutawakil and others (2006), the researchers applied the study tools before the program, and after apply its continued month during the academic year (2017/2018), Data were analyzed using Statistical Package for the Social Sciences (SPSS) some statistical indicators were selected such as arithmetical mean and percentage, Mann- Tenni test, ETA square test, first- order variance analysis Crosscall- Wales, and T test.The study obtain the following results: There were statistically significant differences after the implementation of the electronic games program to improve the IQ of the students of the first class first episode in the Omdurman topical- Khartoum State, for the benefit of post- application, there are differences of statistical significance in the effectiveness of the electronic games program in improving the intelligence of the sample for the benefit of students in the first and second class, based on this, the researchers presented a number of recommendations, the most important of which are: generalization the program on the Khartoum state schools to develop the intelligence of the children of the first episode and encourage the use of electronic games in the process of learning and develop their intelligence skills.
Keywords: electronic games; intelligence; students of the first episode